2021
DOI: 10.1093/femsec/fiab121
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic rather than prokaryotic microbiomes change over seasons in rewetted fen peatlands

Abstract: In the last decades, rewetting of drained peatlands is on the rise worldwide, to restore their significant carbon sink function. Despite the increasing understanding of peat microbiomes, little is known about the seasonal dynamics and network interactions of the microbial communities in these ecosystems, especially in rewetted fens (groundwater-fed peatlands). Here, we investigated the seasonal dynamics in both prokaryotic and eukaryotic microbiomes in three common fen types in Northern Germany. The eukaryotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…S1 ). However, compared with the previous year without drought [ 8 ], these patterns were much stronger in both sites, illustrating that microbiomes are sensitive to (extreme) weather changes in rewetted fens. To gain insights from the functional level, the mRNA transcripts related with stress responses annotated with SEED [ 15 ] were investigated.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…S1 ). However, compared with the previous year without drought [ 8 ], these patterns were much stronger in both sites, illustrating that microbiomes are sensitive to (extreme) weather changes in rewetted fens. To gain insights from the functional level, the mRNA transcripts related with stress responses annotated with SEED [ 15 ] were investigated.…”
mentioning
confidence: 98%
“…Rewetted fen peatlands are locally novel ecosystems [ 7 ], and microbiomes in these ecosystems are still under-characterized. A previous study showed the seasonal dynamics mainly in eukaryotic microbiomes in three rewetted fens [ 8 ], but it remains unclear if this pattern persists in the year with extreme weather events and if the chosen proxy matters in revealing microbiome dynamics.…”
mentioning
confidence: 99%
“…Similar results were found in a grassland system where plant diversity had a weak effect on microbial populations at small distances [ 72 ]. Soil prokaryotic microbiomes were stable across seasons in peatland soil [ 73 ] and in the sands of temperate and polar coastal regions [ 74 ]. The functional predictions made regarding the nitrogen cycle genes and overall bacterial community showed no variations across seasons, following May ( Figure 1 b and Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The edaphic properties including water content and concentrations of dissolved organic matter (DOM), nitrate, nitrite, ammonium, and soluble reactive phosphorus were measured as previously described. , The detected DOM consisted of three groups: (i) biopolymers (BP-S), (ii) humic or humic-like substances including building blocks (HL-S), and (iii) low-molecular-weight substances (LM-S), according to Heinz and Zak . The edaphic properties were measured with samples in April, August, and December 2018.…”
Section: Methodsmentioning
confidence: 99%